Six Legged Walking Robot Simulation and Control - Tomas Michulek; Vojtech Simak; Jan Capak (Communications - Scientific letters of the University of Zilina, 2007)
The authors present the first results of their scientific work related to design and development of the walking robot control systems in virtual reality. Six-legged walking robot was created along with its virtual counterpart simulated in virtual environment. A control system was created and tested on virtual model. This control system was then directly used to control real robotic construction. Differences between real and virtual robot behavior were analyzed.